Practice - Boon, Marcus; Boon, Marcus; Levine, Gabriel, 1975-; Acker, Kathy; Althusser, Louis; Badiou, Alain (London : Whitechapel Gallery, 2018)
Alÿs, Francis ; Araeen, Rasheed ; Arakawa ; Attia, Kader ; Belmore, Rebecca ; Bronson, AA ; Clark, Lygia ; Critical Art Ensemble ; Gates, Theaster ; Gins, Madeline ; Group Material ; Hsieh, Tehching ; Facettes, Huit ; Kelly, Mary ; Montano, Linda M. ; Oliveros, Pauline ; Ono, Yoko ; Piper, Adrian ; Pussy Riot ; Puusemp, Raivo ; Rainer, Yvonne ; Rammellzee ; Schneemann, Carolee ; Shvarts, Aliza ; Situationist International ; Staal, Jonas ; Stelarc ; Tan, Fiona ; Tanaka, Min ; Tjanpi Desert Weavers ; Vicuña, Cecilia ; Womanhouse
boek
Keywords: Art, Modern -- 21st century